The role of the West African dwarf goat in the economy of the smallholder arable farmer in the subhumid zone of Nigeria - Ikwuegbu, O.A.; Tarawali, G.; Njwe, R.M. (International Livestock Centre for Africa, 1993)
This study analysed 875 records of West African Dwarf (WAD) goats owned by 45 farmers and collected over 30 months. In the wet season WAD goats had access to either fodder banks or natural pasture. After crop harvest, animals roamed freely. Litter sizes were 1.67 + 0.08 and 1.56 + 0.06, respectively, on the two grazing systems and were affected by parity (P<0.05). Births accounted for 87% of all entries while multiple births accounted for about 68 % of all kids. Castrates accounted for about 60% of all mature males. Between 35 and 39% of adult goats were sold for meat and offtake accounted for between 51 and 53 % of all exits. Sufficient cash was generated from goat offtake to purchase farm inputs and some household items. Goats play other important roles in the socio-economy of the traditional smallholder farming system.